A swirling jet with vortex breakdown: three-dimensional coherent structures; Thermophysics and Aeromechanics; Vol. 23, iss. 2 - Alekseenko S. V. Sergey Vladimirovich; Dulin V. M.; Tokarev M. P.; Markovich D. M. Dmitry Markovich (2016, 2016)
Title screen